Kualitas Kepemimpinan Guest Service Centre Supervisor Pada Masa Pandemi Covid-19 Di Padma Resort Legian - Ni Komang Widiastari; I Wayan Seniartha; I Gusti Ayu Putu Wita Indrayani (Journal of Hospitality Accommodation Management (JHAM), 2022)
This writing aims to determine the leadership quality of the Guest Service Center Supervisor during the Covid-19 Pandemic at Padma Resort Legian. Data obtained by interview and questionnaire techniques. Data analysis in this study is descriptive qualitative. In this paper, the data obtained are as follows: the results of a questionnaire regarding the leadership quality of the guest service center supervisor during the COVID-19 pandemic at Padma Resort Legian. There are ten dimensions to measure the leadership quality of the guest service center supervisor during the COVID-19 pandemic at Padma Resort Legian.  From the results of the discussion, it can be seen that the dimension "having authority and charisma" gets a score of 2.56 which means it is not good, this is because the supervisor's actions are still not firm to employees, then the dimension "able to make decisions" gets a value of 3.18 which means neutral  , this is because supervisors are still hesitant in acting and have not been optimal in dealing with problems, the dimension of "having initiative" gets a value of 3.25 which means neutral, this is because supervisors lack sensitivity to a problem.  Thus, supervisors are expected to be more assertive in taking action against employees who are less disciplined, accustomed to training themselves by handling their own problems and having a greater sense of initiative.